Pengaruh Food Vlogger dan Promosi Endorse Media Sosial pada Brand Exposure Wisata Kuliner Klaten - Safitri, Lina Ayu; Pradiatiningtyas, Diah; Dewa, Chriswardana Bayu (Jurnal Ilmiah Pariwisata, 2023)
This research aims to determine the influence of food vloggers and social media endorsement promotions on brand exposure for Klaten Culinary Tourism. This research is a quantitative research with a sampling method using purposive sampling. Research data was taken using primary data from questionnaires given to 150 respondents. The variables in this research consist of two independent variables and one dependent variable. The analysis tool uses the SPSS 24 program. The results of this research show that food vloggers can influence brand exposure positively, where the higher the credibility of the food vlogger, the higher the brand exposure. This shows that the credibility of a food vlogger has significant influence in increasing the brand exposure of Klaten culinary tourism. Meanwhile, endorsement promotions have an insignificant positive influence on brand exposure, which means that the higher the credibility of the endorsement promotion media, the more brand exposure will increase by a small amount. These results indicate that the credibility of endorsed promotional media has a low influence on increasing brand exposure for Klaten culinary tourism. It is hoped that this research can provide literature to culinary tourism business managers on the use of food vloggers and endorsement promotions that can be used to market businesses, especially culinary tourism businesses. Keywords: Food Vlogger, Endorse, Exposure, Social Media, Culinary Tourism